Generalized mathematical induction

In summary, the Fibonacci sequence is defined as 1=f0; f1=1 andϕn-ϕ-n=1/sqrt(5)[ϕn-(-ϕ)-n]where ϕ is the golden ratio.
  • #1
Dog1
2
0
Recall that the fibonacci sequence is defined as

{ f0=0; f1 = 1 and
{fn = f n - 1 + fn -2 for n 2

Prove by generalized mathematical induction that

fn = 1/sqrt(5)[ϕn - (-ϕ)-n]

where ϕ = [1+sqrt(5)]/2

is the golden ratio.. (This is known as de Moivre's formula.)
So I'm completely lost as to how I should start this and I need someone to point me in the right direction. Thanks.
 
Physics news on Phys.org
  • #2
First, you want to demonstrate that the base case $P_0$ is true:

\(\displaystyle F_0=\frac{1}{\sqrt{5}}\left(\phi^{0}-\phi^{-0} \right)=0\)

Is this true?

Next, state the induction hypothesis:

\(\displaystyle F_k=\frac{1}{\sqrt{5}}\left(\phi^{k}-(-\phi)^{-k} \right)\)

As your inductive step, the recursive definition of the sequence will be helpful. During this process you will want to demonstrate that:

\(\displaystyle \phi^{k}+\phi^{k-1}=\phi^{k+1}\)

and

\(\displaystyle (-\phi)^{-k}+(-\phi)^{-(k-1)}=(-\phi)^{-(k+1)}\)
 
  • #3
Hi, and welcome to the forum. Please see the section on strong induction in Wikipedia and possibly other sections of that article.
 
  • #4
MarkFL said:
First, you want to demonstrate that the base case $P_0$ is true:

\(\displaystyle F_0=\frac{1}{\sqrt{5}}\left(\phi^{0}-\phi^{-0} \right)=0\)

Is this true?

Next, state the induction hypothesis:

\(\displaystyle F_k=\frac{1}{\sqrt{5}}\left(\phi^{k}-\phi^{-k} \right)\)

As your inductive step, the recursive definition of the sequence will be helpful. During this process you will want to demonstrate that:

\(\displaystyle \phi^{k}+\phi^{k-1}=\phi^{k+1}\)

and

\(\displaystyle \phi^{-k}+\phi^{-(k-1)}=\phi^{-(k+1)}\)

So my base cases check to be true. I've attached my work here.

View attachment 1849

And fn is true for n. But I'm not sure how to prove for n + 1.

fn+1= f(n+1)-1 + f(n+1)-2

=fn+f(n-1)
=1/sqrt(5)[ϕn-n] + 1/sqrt(5) [ϕ(n-1) ϕ-(n-1)

What do I do next? If I'm even going in the right direction.
 

Attachments

  • dog2.jpg
    dog2.jpg
    29.1 KB · Views: 51
Last edited by a moderator:
  • #5
While it didn't hurt to show it is true for $n=1$, you really only need to show it is true for one case, and demonstration that it is true for $n=0$ is simpler.

Okay, next you want to state the induction hypothesis $P_k$:

\(\displaystyle F_k=\frac{1}{\sqrt{5}}\left(\phi^{k}-(-\phi)^{-k} \right)\)

Now, I suggest adding to this $P_{k-1}$

\(\displaystyle F_{k-1}=\frac{1}{\sqrt{5}}\left(\phi^{k-1}-(-\phi)^{-(k-1)} \right)\)

Aided by the recursion:

\(\displaystyle F_{k+1}=F_{k}+F_{k-1}\)

the left side immediately becomes what you need. And the right side also becomes what you need if you prove the two properties involving $\phi$ I listed in my first post are true.
 
  • #6
MarkFL said:
\(\displaystyle F_k=\frac{1}{\sqrt{5}}\left(\phi^{k}-\phi^{-k} \right)\)
This should say
\[
F_k=\frac{1}{\sqrt{5}}\left(\phi^{k}-(-\phi)^{-k} \right)
\]
just as the original post says.

MarkFL said:
While it didn't hurt to show it is true for $n=1$, you really only need to show it is true for one case
Hmm...

MarkFL said:
Okay, next you want to state the induction hypothesis $P_k$:

\(\displaystyle F_k=\frac{1}{\sqrt{5}}\left(\phi^{k}-\phi^{-k} \right)\)

Now, I suggest adding to this $P_{k-1}$

\(\displaystyle F_{k-1}=\frac{1}{\sqrt{5}}\left(\phi^{k-1}-\phi^{-(k-1)} \right)\)
Let's set $k=1$. We have proved $P_0$, but what about $P_1$?
 
  • #7
Evgeny.Makarov said:
This should say
\[
F_k=\frac{1}{\sqrt{5}}\left(\phi^{k}-(-\phi)^{-k} \right)
\]
just as the original post says.

Hmm...

Let's set $k=1$. We have proved $P_0$, but what about $P_1$?

I fixed my posts to correctly state the hypothesis. My mistake also that both given initial values need to be shown are true.
 
  • #8
As as aside, we can derive the required result. If we write the recursion as the linear homogeneous difference equation:

\(\displaystyle F_{n}-F_{n-1}-F_{n-2}=0\)

We then find the associated characteristic equation is:

\(\displaystyle r^2-r-1=0\)

Application of the quadratic formula yields the characteristic roots:

\(\displaystyle r=\frac{-(-1)\pm\sqrt{(-1)^2-4(1)(-1)}}{2(1)}=\frac{1\pm\sqrt{5}}{2}\)

Now, if we define:

\(\displaystyle \phi=\frac{1+\sqrt{5}}{2}\)

We then see that:

\(\displaystyle \frac{1-\sqrt{5}}{2}\cdot\frac{1+\sqrt{5}}{1+\sqrt{5}}= \frac{1-5}{2\left(1+\sqrt{5} \right)}=- \frac{2}{1+\sqrt{5}}=(-\phi)^{-1}\)

Hence the characteristic roots may be given as:

\(\displaystyle r=\phi,\,(-\phi)^{-1}\)

And thus, we know the closed form for $F_n$ is given by:

\(\displaystyle F_n=A\phi^n+B(-\phi)^{-n}\)

Now, using the initial values of the sequence, we may determine the values of the parameters $A$ and $B$:

\(\displaystyle F_0=A\phi^0+B(-\phi)^{-0}=A+B=0\implies B=-A\)

\(\displaystyle F_1=A\phi^1+B(-\phi)^{-1}=A\frac{1+\sqrt{5}}{2}-A\frac{1-\sqrt{5}}{2}=A\sqrt{5}=1\implies A=\frac{1}{\sqrt{5}}\)

Hence, we find the solution satisfying the difference equation and the initial values is:

\(\displaystyle F_n=\frac{1}{\sqrt{5}}\phi^n-\frac{1}{\sqrt{5}}(-\phi)^{-n}\)

Factoring gives us:

\(\displaystyle F_n=\frac{1}{\sqrt{5}}\left(\phi^n-(-\phi)^{-n} \right)\)
 
  • #9
Dog said:
fn = 1/sqrt(5)[ϕn - (-ϕ)-n]

where ϕ = [1+sqrt(5)]/2
Prove that this is the same as \(\displaystyle F_n=\frac{\left(\frac{1+\sqrt{5}}{2}\right)^n-\left(\frac{1-\sqrt{5}}{2}\right)^n}{\sqrt{5}}\).

On induction step calculate \(\displaystyle F_{n+1}=F_{n-1}+F_n\) by using

\(\displaystyle \left(\frac{1+\sqrt{5}}{2}\right)^2=1+\frac{1+ \sqrt{5}}{2}\)

\(\displaystyle \left(\frac{1-\sqrt{5}}{2}\right)^2=1+\frac{1-\sqrt{5}}{2}\)
 

FAQ: Generalized mathematical induction

What is Generalized Mathematical Induction?

Generalized Mathematical Induction is a proof technique used in mathematical logic to prove statements about all natural numbers or other well-ordered sets. It is a generalization of the principle of mathematical induction, and is based on the structure of well-ordered sets.

How does Generalized Mathematical Induction differ from regular Mathematical Induction?

Generalized Mathematical Induction differs from regular Mathematical Induction in that it allows for the use of any well-ordered set, not just the set of natural numbers. This means that it can be applied to a wider range of mathematical statements and problems.

What is the process for using Generalized Mathematical Induction?

The process for using Generalized Mathematical Induction is similar to regular Mathematical Induction. First, you must prove that the statement is true for the first element in the well-ordered set. Then, you must prove that if the statement is true for one element, it is also true for the next element in the set. This process is repeated for all elements in the set.

What are the advantages of using Generalized Mathematical Induction?

The main advantage of using Generalized Mathematical Induction is that it allows for the proof of statements about a wider range of well-ordered sets. This can be useful in solving more complex mathematical problems that cannot be solved using regular Mathematical Induction.

Are there any limitations to using Generalized Mathematical Induction?

One limitation of Generalized Mathematical Induction is that it can only be used for well-ordered sets. This means that it cannot be used for sets that are not well-ordered, such as the set of real numbers. Additionally, it may not be the most efficient method for proving certain statements, as it requires proving the statement for every element in the set.

Similar threads

Replies
4
Views
2K
Replies
8
Views
1K
Replies
5
Views
4K
Replies
5
Views
2K
Replies
4
Views
2K
Replies
11
Views
844
Replies
2
Views
2K
Back
Top